Bis{4-phenyl-1-[1-(pyridin-2-yl-N)ethylidene]thiosemicarbazidato-2N1,S}cadmium - Fonseca, Alexandra de Souza (2012)
The reaction of cadmium acetate dihydrate with 2-acetylpyridine (4-phenylthiosemicarbazone) yielded the title compound, [Cd(C14H13N4S)2]. The CdII atom is six-coordinated in a distorted octahedral environment by two deprotonated thiosemicarbazone ligands acting in a tridentate chelating mode through two N and one S atoms, forming metalla-rings. In the crystal, molecules are connected through inversion centers via pairs of N-HS interactions, building a one-dimensional hydrogen-bonded polymer along [0-1-1].